2014
DOI: 10.1007/s00421-014-2991-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pedal rate on muscle oxygenation, muscle activation and whole-body VO2 during ramp exercise in healthy subjects

Abstract: The present study showed that muscle activation and oxygenation at high intensities during incremental exercise are related to pulmonary VO2 rather than external WR, with a close interrelationship between that muscle activation, oxygenation and pulmonary VO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 47 publications
3
24
1
2
Order By: Relevance
“…On the other hand, previous studies that were interested in the effect of pedaling cadence on muscle oxygenation, by using near-infrared spectroscopy technology (NIRS), reported a similar level of O 2 extraction independently of the cadence during incremental exercise (Ferreira et al 2006) and during moderate exercise (Kounalakis and Geladas 2012;Zorgati et al 2013). Nevertheless, Boone et al (2014) observed a greater muscle O 2 extraction at the highest pedaling cadence during incremental ramp exercise.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…On the other hand, previous studies that were interested in the effect of pedaling cadence on muscle oxygenation, by using near-infrared spectroscopy technology (NIRS), reported a similar level of O 2 extraction independently of the cadence during incremental exercise (Ferreira et al 2006) and during moderate exercise (Kounalakis and Geladas 2012;Zorgati et al 2013). Nevertheless, Boone et al (2014) observed a greater muscle O 2 extraction at the highest pedaling cadence during incremental ramp exercise.…”
Section: Introductionmentioning
confidence: 71%
“…It should be considered that ∆deoxy[Hb + Mb] reflects the balance between V O 2M and Q O 2M (i.e., V O 2M /QO 2M ratio) and thus microvascular O 2 extraction [i.e., proportional to C(a−v)O 2 ] (Boone et al 2014;DeLorey et al 2003;Ferreira et al 2006;Grassi et al 2003;Koga et al 2007) and ∆total[Hb + Mb] reflects the increase in microcirculation hematocrit (Hct) during (Boone et al 2014;Davis and Barstow 2013;Poole et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations